Antioxidant and cytotoxic effects of crude extract, fractions and 4-nerolidylcathecol from aerial parts of pothomorphe umbellata L. (Piperaceae) - Lopes, Andrey P.; Bagatela, Bianca S.; Rosa, Paulo C. P.; Nanayakkara, Dhammika N. P.; Carlos Tavares Carvalho, José; Maistro, Edson Luis [UNESP]; Bastos, Jairo K.; Perazzo, Fábio F. (Hindawi, 2013)
The crude ethanolic extract from aerial parts of Pothomorphe umbellata L. (Piperaceae) and fractions obtained by partitions sequentially among water-methanol, methylene chloride, and ethyl acetate, as well as the major constituent, 4-nerolidylcatechol, were, respectively, evaluated and evidenced for antioxidant and cytotoxic effects through fluorometric microplate and microculture tetrazolium assays in HL-60 cells. The crude ethanolic extract demonstrated the preeminent antioxidant activity (IC50 = 1.2 μg/mL) against exogenous cytoplasmic reactive oxygen species, followed by the water-methanolic (IC50 = 4.5 μg/mL), methylene chloride (IC 50 = 5.9 g/mL), ethyl acetate (IC50 = 8.0 g/mL), 4-nerolidylcatechol (IC50 = 8.6 g/mL), and the sterol fractions (IC50 > 12.5 μg/mL). Vitamin C, the positive control used in this assay, presented IC50 value equivalent to 1.7 μg/mL. 4-Nerolidylcatechol (IC50 = 0.4 μg/mL) and methylene chloride fraction (IC50 = 2.3 μg/mL) presented considerable cytotoxicity probably because of the presence of an o-quinone, an auto-oxidation by product of the catechol. Polar compounds, present in the ethanol extract, appear to increase the solubility and stability of the major active constituent, acting synergistically with 4-nerolidylcatechol, improving its pharmacokinetic parameters and increasing significantly its antioxidant activity which, in turn, suggests that the aqueous-ethanolic extract, used in folklore medicine, is safe and effective. © 2013 Andrey P. Lopes et al.
Keywords: 4 nerolidylcatechol; acetic acid ethyl ester; alcohol; catechol derivative; dichloromethane; plant extract; Pothomorphe umbellata plant extract; sterol; unclassified drug; antioxidant activity; controlled study; cytotoxicity; drug solubility; drug stability; human; human cell; medicinal plant; oxidation; Piperaceae; plant leaf; Pothomorphe umbellata